Glitches in the brain: the dangerous relationship between radiotherapy and brain fog - Marino, Noemi; Bedeschi, Martina; Vaccari, Melania Elettra; Cambiaghi, Marco; Tesei, Anna (Frontiers in Cellular Neuroscience, 2024)
Up to approximately 70% of cancer survivors report persistent deficits in memory, attention, speed of information processing, multi-tasking, and mental health functioning, a series of symptoms known as "brain fog". The severity and duration of such effects can vary depending on age, cancer type, and treatment regimens. In particular, every year, hundreds of thousands of patients worldwide undergo radiotherapy (RT) for primary brain tumors and brain metastases originating from extracranial tumors. Besides its potential benefits in the control of tumor progression, recent studies indicate that RT reprograms the brain tumor microenvironment inducing increased activation of microglia and astrocytes and a consequent general condition of neuroinflammation that in case it becomes chronic could lead to a cognitive decline. Furthermore, radiation can induce endothelium reticulum (ER) stress directly or indirectly by generating reactive oxygen species (ROS) activating compensatory survival signaling pathways in the RT-surviving fraction of healthy neuronal and glial cells. In particular, the anomalous accumulation of misfolding proteins in neuronal cells exposed to radiation as a consequence of excessive activation of unfolded protein response (UPR) could pave the way to neurodegenerative disorders. Moreover, exposure of cells to ionizing radiation was also shown to affect the normal proteasome activity, slowing the degradation rate of misfolded proteins, and further exacerbating ER-stress conditions. This compromises several neuronal functions, with neuronal accumulation of ubiquitinated proteins with a consequent switch from proteasome to immunoproteasome that increases neuroinflammation, a crucial risk factor for neurodegeneration.The aetiology of brain fog remains elusive and can arise not only during treatment but can also persist for an extended period after the end of RT. In this review, we will focus on the molecular pathways triggered by radiation therapy affecting cognitive functions and potentially at the origin of so-called "brain fog" symptomatology, with the aim to define novel therapeutic strategies to preserve healthy brain tissue from cognitive decline.